Environmental Disclosure Practices in Publicly Traded Companies of Bangladesh - Shakhawat Hossain Sarkar; Razu Ahmed; Md. Ashraful Alam (Indonesian Journal of Sustainability Accounting and Management, 2023)
This study strives to identify the level of corporate environmental disclosures and their relationship with various corporate attributes using secondary data sources. The data for this study were collected under the dichotomous procedure through content analysis of the annual reports of 190 companies. The statistical results depict that the practice of the Environmental Disclosure Index (EDI) is poor, with the banking sector securing the highest and the IT sector unveils the lowest EDI observed under the study. The regression model implies that company category, company nature, profit after tax, dividend nature, ISO 14001 certification, company age, capital employed, and total revenue are statistically significant. However, net assets value per share and multi-nationality are statistically insignificant. The research will provide valuable guidance to policymakers in formulating appropriate policies for safeguarding society through the protection and reduction of environmental degradation. It will improve the livability of the Earth for future generations. Additionally, it will aid the corporate sector in implementing measures to reduce environmental pollution resulting from their activities. This research investigates the intensity of environmental consciousness among corporations in Bangladesh and reveals the link between corporate attributes and environmental disclosure.